2022
DOI: 10.1021/acs.langmuir.2c01790
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic Membranes to Address the Challenges of Salinity Gradient Energy Harvesting: Roles of Nanochannel Geometry and Bipolar Soft Layer

Abstract: Researchers are looking for new, clean, and accessible sources of energy due to rising global warming caused by the usage of fossil fuels and the irreversible harm that this does to the environment. Water salinity is one of the newest and most accessible renewable energy sources, which has sparked a lot of interest. Reverse electrodialysis (RED) has been utilized in the past to turn saline water into electricity. NRED, a reverse electrodialysis method utilizing nanofluidics, has gained popularity as nanoscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…For the PEL domain normal∇ · ( ε P E L ψ ) = prefix− F i = 1 4 z i c i σ normalP normalE normalL Here, σ PEL is the PEL space charge density and c i and z i are concentration and valance of the i th ionic species, respectively. Moreover, the value of electrical permittivity ratio is taken as ε PEL /ε v = 0.2 and ε v = 80ε 0 …”
Section: Mathematical Formulationmentioning
confidence: 99%
“…For the PEL domain normal∇ · ( ε P E L ψ ) = prefix− F i = 1 4 z i c i σ normalP normalE normalL Here, σ PEL is the PEL space charge density and c i and z i are concentration and valance of the i th ionic species, respectively. Moreover, the value of electrical permittivity ratio is taken as ε PEL /ε v = 0.2 and ε v = 80ε 0 …”
Section: Mathematical Formulationmentioning
confidence: 99%
“…It is found that each of these shapes leads to the optimization of one of the key indicators. Another major research interest in this area is assessing the effect of soft micro/nanoconduits, and how such systems can play a key role in salinity energy generation (SEG) and energy harvesting [11][12][13]. The system considered was a polyelectrolyte layer (PEL) grafted nanofluidic confinement, and it was revealed that augmentation in the temperature and concentration ratios leads to increase in the SEG.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lab-on-a-chip (LOC) and lab-on-a-disk (LOD) have attracted considerable interest . The development of microchips and nanochips will allow science to do its needed tasks with greater precision, speed, and economy. In contrast, the development and modification of nanochannel structures to create blue energy, , purification of fluids, biosensors, , ion diodes, , ion sensors, and smart ion gates have been significantly advanced during the past decade. , …”
Section: Introductionmentioning
confidence: 99%